(Un)ready for change? The debate about electronic voting in Portugal and its implementation before and after the pandemic era - Lisi, Marco (2022)
The use of electronic voting has been considered an important tool to improve electoral processes in some circumstances, with potential effects in party-voter linkages and participation. However, many countries are skeptical in adopting this digital tool and there are relevant shortcomings in the implementation of electronic voting. Despite favorable conditions for the innovation in voting mechanisms, Portugal is one of the countries still considering the possibility to introduce e-voting. This study argues that we need to consider not only the context in which e-voting takes place, but also the key role of party agents. Drawing on interviews with party officials and experts, primary data collection and media sources, this paper shows that in Portugal e-voting is not regarded as a potential tool to improve the electoral process due to the high level of trust and quality of traditional voting mechanisms, as well as due to the divergent interest of political parties. In addition, party organizations are not familiar with the use of digital tools in terms of grassroot mobilization. Overall, the findings indicate that party barriers are also key for allowing the (non)adoption of e-voting.